2021
DOI: 10.18632/aging.202874
|View full text |Cite
|
Sign up to set email alerts
|

Long intergenic noncoding RNA 00665 promotes proliferation and inhibits apoptosis in colorectal cancer by regulating miR-126-5p

Abstract: Long intergenic noncoding RNAs (lincRNAs) regulate a series of biological processes, and their anomalous expression plays critical roles in the progression of multiple malignancies, including colorectal cancer (CRC). Although many studies have reported the oncogenic function of LINC00665 in multiple cancers, few studies have explored its role in CRC. The aim of this study was to assess the effect of LINC00665 on the malignant behaviors of CRC and explore the underlying regulatory mechanism of LINC00665. LINC00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“… Wu et al (2021) measured the expression of LINC00665 by qRT-PCR in 67 colorectal cancer tissues and their matched adjacent healthy tissues. They found significant upregulation of LINC00665 in colorectal cancer tissues compared to healthy control tissues.…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%
See 4 more Smart Citations
“… Wu et al (2021) measured the expression of LINC00665 by qRT-PCR in 67 colorectal cancer tissues and their matched adjacent healthy tissues. They found significant upregulation of LINC00665 in colorectal cancer tissues compared to healthy control tissues.…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%
“…They found that the high expression of LINC00665 in tumor tissues was significantly related to regional lymph node metastasis and poor colorectal cancer tissue differentiation in patients. Experiments in vitro revealed that LINC00665 knockdown could inhibit the proliferation, migration, and invasion of colorectal cancer cells and induce apoptosis in colorectal cancer cells ( Zhao et al, 2020c ; Han et al, 2021 ; Wu et al, 2021 ). Mechanistically, researchers used StarBase to predict the targeted miRNA of LINC00665 and found that miR-9-5p was one of the candidate targets of LINC00665 ( Zhao et al, 2020c ).…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%
See 3 more Smart Citations